Gradually shrinking intra-abdominal desmoid tumor derived from the stomach in a young boy: a case report - Kazushi Miyata; Masahide Fukaya; Masato Nagino (Surgical Case Reports)
Abstract Background Intra-abdominal desmoid tumors, particularly those derived from the stomach, are rare. Such tumors are associated with a history of familial adenomatous polyposis (FAP), trauma, or surgical procedures in general. In addition, spontaneous shrinking of an intra-abdominal desmoid tumor is rarer. And desmoid tumors most commonly arise during the fourth decade of life. Case presentation A 17-year-old boy with lower abdominal pain was diagnosed with a gastrointestinal stromal tumor (GIST) or a hematoma at a local hospital. He had no history of FAP, trauma, or previous surgery. Abdominal computed tomography (CT) was performed for observational purposes three times over a 9-month period. The tumor gradually decreased in size over time; however, the tumor did not shrink sufficiently to be diagnosed as a hematoma. Because there was a high possibility of a GIST from the stomach, he underwent laparotomy. Operative findings revealed that the tumor was a hard mass firmly attached to both the greater curvature of the stomach and the inferior pole of the spleen. Pathologically, the tumor was diagnosed as a desmoid tumor derived from the stomach. Conclusion For a young boy without a history of FAP, trauma, or surgical procedures, it is difficult to define an intra-abdominal tumor near the stomach as a desmoid tumor. In such cases, surgical resection is recommended for a definitive diagnosis.